Effectiveness of a participatory physical and psychosocial intervention to balance the demands and resources of industrial workers: A cluster-randomized controlled trial - Gupta, Nidhi; Wåhlin-Jacobsen, Christian Dyrlund; Abildgaard, Johan Simonsen; Henriksen, Louise Nøhr; Nielsen, Karina; Holtermann, Andreas (Scandinavian Journal of Work, Environment ＆ Health, 2018)
Objectives The aim of this study was to evaluate the effectiveness of a participatory physical and psychosocial workplace intervention (known as PIPPI) on work ability and recovery among industrial workers. Methods Eligible workers were cluster-randomized into intervention (N=193) and control (N=222) groups. Intervention group members participated in three workshops where they mapped positive and negative aspects of their physical and psychosocial work environment and developed action plans addressing the highlighted issues, which were subsequently implemented by the participants. Questionnaire-based data on work ability and recovery were collected at baseline and 8-, 10- and 12-month follow-up. Data on productivity, well-being, mental health, and physical demands and resources were collected at baseline and 12-month follow-up. Results The intervention was delivered and received as planned (100% planned workshops conducted, 69% [standard deviation (SD) 7%] participation in workshops) and with a response rate of 76% (SD 8%) to the questionnaires. No significant between-group improvements for any of the outcomes were found in intention-to-treat multi-level mixed models. On the contrary, tendencies were observed for poorer recovery and reduced work ability in the intervention compared to control group. Conclusion The intervention did not improve the outcomes. This result can have several explanations, such as a regression-toward-the-mean effect or that the intervention might have put an additional burden on the workers already facing high work demands. In addition, there may have been an insufficient match between the intervention components implemented and the predetermined outcomes, and implementation may have been unsuccessful. These potential explanations need to be investigated using process evaluation data.